Pengaruh Arsitektur Tradisional Jawa dalam Hunian Kolonial di Kampung Bubutan Surabaya - Risqi Cahyani; Lisa Dwi Wulandari; Antariksa Antariksa (RUAS (Review of Urbanism and Architectural Studies), 2015)
Kampung Bubutan is one of the original community of settlements in the city of Surabaya. As the coastal city, Surabaya closely with the image as a trading city. These factors led many immigrants come from many different cultures, local and international including Netherlands. This article will discuss about what makes the formation of the settlement pattern at Kampung Bubutan, and how the acculturation between Javanese and Colonial on the settlement using descriptive–qualitative method. The results is Kali Mas river and Mancapat mythe effected the formation of Kampung Bubutan settlements. Colonial architectural found in the basic shape of the building and building technology . While the Javanese architecture found in the building ornaments, organizations of space, and the meaning of the Javanese who appreciate nature and social community. Values, advices, and good wises from Javanese giving much meaning in the house.Keywords: Javanese architecture, colonial architecture, etnic aculturation